Analysis of Profile Karang Taruna as Part of Learning Needs Assessment to Accelerate the Enhancement of Human Resources Development - Hasan, Fuad; Hendrawijaya, Arief Tukiman; Himmah, Irliana Faiqotul; Purnamawati, Frimha (Journal of Nonformal Education, 2020)
The existence of Karang taruna is to help the Indonesian Government to provide social welfare is still debate able because of the various condition of Karang taruna. This research aimed to identify and analyze learning needs of Karang Taruna based on its profile that is divided by managerial role, administrative, and entrepreneurship. This research use mix method with the descriptive design. The steps of this research are (1) preliminary study, (2) formulating questionnaire, (3) collecting quantitative data, (4) analyzing quantitative data, (5) collecting qualitative data, (6) analyzing qualitative data, and (7) taking conclusion. The result of this research is (1) at managerial role, developing Karang taruna is need improvement almost in all sub aspect while developed and pilot Karang taruna need improvement in some aspect, (2) at administrative aspect, developing Karang taruna need improvement almost in all aspect while developed and pilot Karang taruna need improvement in some aspect, (3) at entrepreneurship aspect, developing, developed and pilot Karang taruna need improvement almost in all aspects. It can be concluded that all Karang taruna still need improvement at managerial, administrative, and entrepreneurship aspects. So this research provides information that to enhance the human resource development Karang taruna should improve their performance, especially at managerial, administrative, and entrepreneurship aspect. It also suggests the social office to provide development program for Karang taruna based on the weak aspect of Karang taruna. This research also strengthens the implementation of models for developing Karang taruna especially about the learning material that should be delivered.